A review of the genus Microdera Eschscholtz, 1831 (Coleoptera: Tenebrionidae) of Uzbekistan - Bekchanov, Norbek Kh.; Nabozhenko, Maxim V.; Bekchanov, Khudaybergan U.; Bekchanova, Mokhira Kh. (Zootaxa, 2025)
A review of darkling beetles of the genus Microdera Eschscholtz, 1831 from Uzbekistan is presented. In total, 12 species are known in this country. Two new species are described: M. abdullohi N. Bekchanov et Nabozhenko, sp. nov. (Sulton Uvays Mts.) and M. uzbekistanica N. Bekchanov et Nabozhenko, sp. nov. (Kuldzhuktau Mts.). The following new synonym is introduced: Microdera globulicollis Ménétriés, 1849 = Microdera extabesa Skopin, 1961, syn. nov. The species M. ferghanensis Kaszab, 1957 is resurrected from the synonymy of M. globulicollis Ménétriés, 1849. In describing the ranges of the species mentioned in the paper, we corrected some errors in previous publications and clarified the distribution, including as a result of taxonomic changes. A species rank status is restored for Microdera kaszabi Skopin, 1961, stat. resurr. (from a subspecies of M. convexa (Tauscher, 1812)), as a consequence the range of this species does not include southeastern Kazakhstan, and limited by Kazakh Hummocks in the east. Microdera deserta deserta (Tauscher, 1812) is recorded for Uzbekistan for the first time, and M. shasenema Medvedev & Nepesova, 1985 is firstly recorded for Tajikistan. The following species are removed from faunistic lists of different countries: M. laevigatula Reitter, 1915 from the list of Uzbekistan, M. heydeni Kraatz, 1882 from the list of Turkmenistan, M. minax Reitter, 1887 from the list of Kyrgyzstan, M. transversicollis Reitter, 1887 from the list of Armenia. Lectotypes for Tentyria deplanata Gebler, 1841 and Microdera semenoviana Bogatchev, 1947 are designated.